Corrationalisme: la dimension sociale de l’épistémologie bachelardienne - Ienna, Gerardo (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
In recent years, a new branch of research called Social Epistemology has emerged, finding its genesis in the attempt to rectify standard epistemological theories in the light of a serious consideration of the theoretical nexus of the relationship between knowledge and society. This question had already been addressed – with different tonalities – by many authors active in the first decades of the 20th century, such as Boris Hessen, Edgar Zilsel, Ludwik Fleck, Robert K. Merton, etc. In this context, the social dimension of Bachelardian historical epistemology is a theme that has been largely neglected, both in the vast critical literature on this author and in studies on the relation between knowledge and society. This lack is particularly paradoxical when one considers that Bachelardian thought has inspired epistemological-social theories such as those of Althusser, Foucault and Bourdieu. The objective of this article is to highlight – through a recognition in the corpus of works of this author – the organic relation between the social and historical dimensions in the construction of Bachelard’s epistemological paradigm. In the following pages, it will be construction of a non-Cartesian theory of knowledge based on the idea of the cogitamus, passing through the highlighting of the modalities according to which the union of the workers of the proof constitutes the scientific facts (the founding act of the corrationalism), arrives to conceive a description – that anticipates the much later sociology of the sciences – of the structures and the models of functioning of the scientific communities that he proposes to call “scientific city”. highlighted how this author elaborates a dialectically circular path that, starting from the